Inequalities in the use of secondary prevention of cardiovascular disease by socioeconomic status: evidence from the PURE observational study - Adrianna Murphy, PhD; Benjamin Palafox, MSc; Owen O'Donnell, ProfPhD; David Stuckler, ProfPhD; Pablo Perel, PhD; Khalid F AlHabib, ProfMBBS; Alvaro Avezum, ProfPhD; Xiulin Bai, BSc; Jephat Chifamba, ProfDPhil; Clara K Chow, ProfPhD; Daniel J Corsi, PhD; Gilles R Dagenais, MD; et al. (The Lancet Global Health, 2018)
Summary: Background: There is little evidence on the use of secondary prevention medicines for cardiovascular disease by socioeconomic groups in countries at different levels of economic development. Methods: We assessed use of antiplatelet, cholesterol, and blood-pressure-lowering drugs in 8492 individuals with self-reported cardiovascular disease from 21 countries enrolled in the Prospective Urban Rural Epidemiology (PURE) study. Defining one or more drugs as a minimal level of secondary prevention, wealth-related inequality was measured using the Wagstaff concentration index, scaled from −1 (pro-poor) to 1 (pro-rich), standardised by age and sex. Correlations between inequalities and national health-related indicators were estimated. Findings: The proportion of patients with cardiovascular disease on three medications ranged from 0% in South Africa (95% CI 0–1·7), Tanzania (0–3·6), and Zimbabwe (0–5·1), to 49·3% in Canada (44·4–54·3). Proportions receiving at least one drug varied from 2·0% (95% CI 0·5–6·9) in Tanzania to 91·4% (86·6–94·6) in Sweden. There was significant (p<0·05) pro-rich inequality in Saudi Arabia, China, Colombia, India, Pakistan, and Zimbabwe. Pro-poor distributions were observed in Sweden, Brazil, Chile, Poland, and the occupied Palestinian territory. The strongest predictors of inequality were public expenditure on health and overall use of secondary prevention medicines. Interpretation: Use of medication for secondary prevention of cardiovascular disease is alarmingly low. In many countries with the lowest use, pro-rich inequality is greatest. Policies associated with an equal or pro-poor distribution include free medications and community health programmes to support adherence to medications. Funding: Full funding sources listed at the end of the paper (see Acknowledgments).